2021
DOI: 10.1126/sciadv.abe9733
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the living plant mesophyll into a photonic capacitor

Abstract: Living plants provide an opportunity to rethink the design and fabrication of devices ordinarily produced from plastic and circuit boards and ultimately disposed of as waste. The spongy mesophyll is a high -surface area composition of parenchyma cells that supports gas and liquid exchange through stomata pores within the surface of most leaves. Here, we investigate the mesophyll of living plants as biocompatible substrates for the photonic display of thin nanophosphorescent films for photonic applications. Siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Another popular application is sustainable product design and work aimed at contributing to the circular economy. Such work often investigates the efcacy and feasibility of leveraging plants as fabrication materials [149] or substitute components of more familiar technologies such as conductive wires [13], information displays [42,69], space lighting [44] or data storage centers [7]. Plants are a natural choice here, owing to their inherently biocompatible and biodegradable natures.…”
Section: Application Contextmentioning
confidence: 99%
“…Another popular application is sustainable product design and work aimed at contributing to the circular economy. Such work often investigates the efcacy and feasibility of leveraging plants as fabrication materials [149] or substitute components of more familiar technologies such as conductive wires [13], information displays [42,69], space lighting [44] or data storage centers [7]. Plants are a natural choice here, owing to their inherently biocompatible and biodegradable natures.…”
Section: Application Contextmentioning
confidence: 99%
“…The authors demonstrated that the particles could be charged and discharged within the plant for 16 h a day (2016 cycles) for 2 weeks without any effect on plant physiology. 155 …”
Section: Plant-based Biohybrid Systemsmentioning
confidence: 99%
“…A more recent example of implanted biofuel cells in plants had an increased power output with the use of large electrodes (3.75 cm 2 ) implanted in orange. 155 The anode electrodes were engineered for non-mediated electron transport by using pyrroloquinoline-quinone (PQQ)-dependent glucose dehydrogenase and flavin adenine dinucleotide (FAD)-dependent fructose dehydrogenase that are also oxygen-independent enzymes. The anode could therefore harvest energy from two different sugars sources found in oranges, glucose and fructose, without relying on the dissolved oxygen concentration.…”
Section: Energy Harvesting From Living Plantsmentioning
confidence: 99%
“…6 Efforts in plant nanobionics have also focused on producing novel, living devices based on a symbiosis between nanotechnology and plants. Examples include nanotechnology enabled light-emitting plants 7,8 as well as plants as internet-enabled networks of sensors that can monitor external threats such as explosives. 9 Plants represent an appealing starting platform for these purposes because they continuously grow, self-repair, harvest energy, pump and circulate water, generate their own biofuel and are ultimately carbon negative.…”
Section: Introductionmentioning
confidence: 99%